Influência da sanitização e do armazenamento nos compostos bioativos de manga 'palmer' in natura e processada - Monaco, Kamila de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to investigate the influence of sanitizers (ozone and sodium hypochlorite) in the bioactive compounds content and antioxidant activity during cold storage and marketing simulation grown in mango (Mangifera indica L.) grown in organic and conventional system and verify changes during storage of two different smoothies. To achieve this thesis objective was divided into five sections, the first the mango 'Palmer' organic acquired in Borborema-SP and conventional, donated by Ogata Citrus (Taquaritinga-SP) were transported to the laboratory of Biochemistry, which were submitted four immersion treatments: immersion in water; in chlorinated water with 100 mg L-1 of sodium hypochlorite for 10 minutes and ozonated water for 10 and 20 minutes. The evaluations were performed after harvest and at 7 and 15 days of cold storage. At 7 days, fruit were taken to the environment and evaluations followed by 4 and 8 days, to simulate marketing period. Were determined firmness, pH, ascorbic acid, soluble solids, titratable acidity, total polyphenols, total flavonoids, β-carotene, DPPH and FRAP. The microbiological analyzes were carried out after harvest, after 7 days of cold storage and 7 days over 4 environment. The design was completely randomized (CRD) with factorial 5 x 8 (day trial x treatments) with three repetitions. There was a trend of organic fruit and ozonated have higher bioactive compounds contents, therefore higher antioxidant activity, which shows that ozone could replace chlorine without damage to fruit. In the second chapter, it performed the bioactive amines quantification of the pulp mango 'Palmer' organic and conventional, undergo four sanitization treatments: immersion in the tap water; in chlorinated water with 100 mg L-1 of sodium hypochlorite for 10 minutes and ozonization for 10 and 20 minutes postharvest and after seven days of cold storage followed by 4 and 8 ...

O objetivo deste estudo foi verificar a influencia de sanitizantes (ozônio e hipoclorito de sódio) no conteúdo de compostos bioativos e na atividade antioxidante durante o armazenamento refrigerado e na simulação de comercialização de mangas (Mangifera indica L.) 'Palmer' cultivadas em sistema orgânico e convencional e verificar as alterações durante o armazenamento de dois diferentes smoothies. Para atingir esse objetivo a tese foi dividida em cinco capítulos, no primeiro as mangas 'Palmer' orgânicas adquiridas no município de Borborema-SP e as convencionais, doadas pela Ogata Citrus (Taquaritinga-SP) foram transportadas ao laboratório de Bioquímica, onde foram submetidas a quatro tratamentos de imersão: imersão em água; em água clorada com 100 mg L-1 de hipoclorito de sódio por 10 minutos e em água ozonizada por 10 ou 20 minutos. As avaliações foram realizadas após a colheita e aos 7 e 15 dias de armazenamento refrigerado. Aos 7 dias, os frutos foram levados ao ambiente e as avaliações seguiram por 4 e 8 dias, para simular o período de comercialização. Determinaram-se a firmeza da polpa, pH, ácido ascórbico, sólidos solúveis, acidez titulável, polifenóis totais, flavonóides totais, β-caroteno, DPPH e FRAP. As análises microbiológicas foram realizadas após a colheita, aos 7 dias de armazenando refrigerado e aos 7 dias mais 4 em ambiente. O delineamento utilizado foi inteiramente casualizado (DIC) com esquema fatorial 5 x 8 (dias de avaliação x tratamentos) com 3 repetições. Houve uma tendência dos frutos orgânicos e ozonizados apresentarem maiores conteúdos dos compostos bioativos, com isso maior atividade antioxidante, o que evidenciou que o ozônio pode substituir o cloro sem prejuízos aos frutos. No segundo capitulo, foi realizada a quantificação das aminas bioativas das polpas de manga 'Palmer' orgânicas e convencionais, submetidas a ...
Sanitizers and storage influence in mango 'palmer' in natura and processed bioactive compounds
Keywords: Água - Purificação - Ozonização; Manga (Fruta) - Pos colheita; Agricultura organica; Antioxidantes; Water Purification Oxidation